PEMBELAJARAN FISIKA MELALUI MODEL PROBLEM BASED LEARNING (PBL) DISERTAI PETA KONSEP DI MAN 2 JEMBER (Pada Pokok Bahasan Kinematika Gerak Lurus) - Daimatul Makrifah; Sudarti Sudarti; Subiki Subiki (FKIP Universitas Jember, 2017)
This research aimed to assess the effect of Problem Based Learning (PBL) model with concept mapping on cognitive learning outcomes of student and learning activities of student in physic learning at MAN 2 Jember. This type of research is experimental research by post-test only control design. Population in this study were students of class X at MAN 2 Jember. The research conducted on odd semester of academic year 2016/2017. Samples were taken with cluster random sampling. The methods to collect data in this research are test, observation, interviews and documentation. The cognitive learning outcomes were obtained from control and experimental classesby the post-test. The technique of data analysis cognitive learning outcomes with independent samples t-test. The significance value (1-tailed) <0.05 is 0.0115 <0.05, it can be concluded model of Problem Based Learning (PBL) with concept mapping effect on cognitive learning outcomes of student in physic learning at MAN 2 Jember. Learning activities of student were obtained from observed. The technique of data analysis learning activities of student with independent samples t-test. The significance value (1-tailed) <0.05 is 0.004 <0.05, it can be concluded model of Problem Based Learning (PBL) with concept mapping effect on learning activities of student in physic learning at MAN 2 Jember. Keywords: Problem Based Learning model, concept mapping, cognitive learning outcomes, learning activities of student.